2016
DOI: 10.1155/2016/2678017
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Endothelin-1 Levels in Normal Tension Glaucoma and Primary Open-Angle Glaucoma: A Meta-Analysis

Abstract: Purpose. The aim of this meta-analysis was to clarify the association between the plasma endothelin-1 level and the risks of normal tension glaucoma (NTG) and primary open-angle glaucoma (POAG). Methods. Relevant publications were collected from three databases including PubMed, EMBASE, and the Web of Science through December 31, 2015. In this study, the terms “(endothelin OR ET) AND glaucoma” were searched. Review Manager 5.2 was used to process the data. Results. Seven studies (212 cases, 164 controls) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 30 publications
(43 reference statements)
1
27
0
2
Order By: Relevance
“…In 2016, Li et al [24] performed a meta-analysis in order to combine and summarize the results from several studies analyzing ET-1 plasma levels in NTG patients (7 studies, 212 NTG, 164 controls) and POAG (5 studies, 160 POAG, 174 controls), and also to clarify the association between ET-1 plasma levels and the risk for the mentioned types of glaucoma. They found statistically significant higher ET-1 plasma concentrations in glaucoma patients than in the control group, with a 0.63 pg/ mL mean difference (p = 0.02) in the POAG group, and 0.60 pg/mL (p = 0.007) in the NTG patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2016, Li et al [24] performed a meta-analysis in order to combine and summarize the results from several studies analyzing ET-1 plasma levels in NTG patients (7 studies, 212 NTG, 164 controls) and POAG (5 studies, 160 POAG, 174 controls), and also to clarify the association between ET-1 plasma levels and the risk for the mentioned types of glaucoma. They found statistically significant higher ET-1 plasma concentrations in glaucoma patients than in the control group, with a 0.63 pg/ mL mean difference (p = 0.02) in the POAG group, and 0.60 pg/mL (p = 0.007) in the NTG patients.…”
Section: Resultsmentioning
confidence: 99%
“…ET-1 plasma concentrations in POAG patients reported in other studies. were associated with significantly higher risk for NTG and POAG [24]. In 2016, Kosior-Jarecka et al [27] reported positive correlation between ET-1 plasma levels and visual field defects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single nucleotide polymorphisms (SNPs) in both the ET-1 and ET A receptor genes that affected ET-1 plasma concentrations and higher ET-1 levels correlated with increased visual field damage 42 . A recent meta-analysis that included seven studies (212 cases, 164 controls) for normal tension glaucoma and six studies (160 cases, 174 controls) for the POAG analysis demonstrated increased circulating ET-1 levels in glaucoma patients, compared to control subjects 43 .…”
Section: Discussionmentioning
confidence: 99%
“…One important factor is a disturbed ocular blood flow. Some papers indicated that elevated plasma endothelin-1, which is known as a vasoconstrictor that increases under hypoxia, is involved in patients with NTG [28] , and a local increase of endothelin-1 can result in the occurrence of retinal vein occlusion through increased retinal venous pressure [29] . The pathomechanisms of NTG and POAG are different, and this needs further investigation; however, atherosclerosis or systemic hypertension, besides the disturbed autoregulation of optic nerve head circulation in patients with NTG and POAG, might induce CRVO.…”
Section: Discussionmentioning
confidence: 99%